Transparent Silver Coatings with Copper Addition for Improved Conductivity by Combined DCMS and HiPIMS Process - Catalin Vitelaru; Anca C. Parau; Mihaela Dinu; Iulian Pana; Lidia R. Constantin; Arcadie Sobetkii; Iulian Iordache (Metals, 2022)
The demand for transparent conductive coatings has increased over recent years, leading to the development of various technical solutions. One of the approaches is to use metallic coatings very close to their coalescence thickness, so that a good compromise between transparency and conductivity is obtained. In this contribution, a combination of two elements with high potential in this field is used, namely silver and copper. The continuity of silver films on a dielectric transparent substrate is significantly improved by the addition of a copper seed layer that promotes the formation of a continuous layer at smaller effective thicknesses. Two distinct deposition processes are used for the deposition of the two materials, namely HiPIMS (High Power Impulse magnetron sputtering) for copper and DC sputtering for silver. The use of HiPIMS enables a better control of the structure and quantity of deposited material, allowing us to deposit a very small amount of material. The mono-element coatings are characterized from the optical and electrical point of view, and then mixed to form a structure with better transparency, up to 80% in the visible spectrum, good electrical properties, resistivity of ~2 × 10−5 (Ω × cm), and significantly lower surface roughness, down to 0.2 nm.